Development of Analytical Framework for MIMO-OFDM System in Fading Environment - Singh, Daljeet (TIET, 2019)
The use of wireless communication has extended from traditional voice calling and short message service to high-speed internet, machine-to-machine communication, and real-time applications like online gaming, video conferencing, e-commerce transactions, voice over internet protocol, chatting, and instant messaging. As a result, the number of distinct users who communicate through wireless media has increased substantially over the last few years. These recent innovations in mobile systems have pushed the current fourth-generation communication systems to achieve even higher throughput. Maintaining the required quality of service for reliable and secure communication is the major challenge among the research fraternity. In order to fulfill these needs of wireless communication, many current and future standards have adopted multicarrier techniques like orthogonal frequency-division multiplexing (OFDM) along with multiple-input-multiple-output (MIMO) system. This combination is known as MIMO-OFDM system, which has advantages of both MIMO and OFDM. MIMO can be implemented effectively with the help of different coding techniques in time and/or frequency domain. In this dissertation, an analytical framework for MIMO-OFDM systems is presented. It includes the study of di erent types of MIMO-OFDM systems and the various sub-blocks that are used to implement these systems. With the aid of the analytical framework de-vised in this work, the performance of MIMO-OFDM systems is calculated. The second contribution of this thesis is the introduction of a uni ed approach for obtaining the performance analysis of MIMO-OFDM system. This approach was introduced for both space frequency block coded and space time block coded OFDM systems. The performance of MIMO-OFDM systems can be calculated for any given fading scenario using the proposed approach due to the usage of generalized channels. The third contribution of this thesis is the study of MIMO-OFDM systems under the effect of channel impairments like carrier frequency offset and unavailability of perfect channel state information. The analytical results obtained from the derived expressions are verified using Monte Carlo simulations. The results obtained by the proposed uni ed approach are obtained mostly in closed-form expressions. In some cases, numerical integration is required to be calculated over finite limits. This is very easily implemented with ignorable error using tools like MATLAB and Mathematica.
Doctoral Thesis of Mr. Daljeet Singh
Keywords: OFDM; MIMO; SFBC; STBC; BER